2019
DOI: 10.1371/journal.pone.0216344
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean delivery among women who gave birth in Dessie town hospitals, Northeast Ethiopia

Abstract: Background One of the key strategies for reducing maternal and perinatal morbidities and mortalities is the provision of skilled intrapartum care. While cesarean section is an important emergency obstetric intervention for saving the lives of mothers and newborns, a study comparing the prevalence of cesarean delivery is not sufficiently available in Ethiopia. This study aimed at assessing the prevalence and associated factors of cesarean delivery among women who gave birth at hospitals in Dessie t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 28 publications
(27 reference statements)
7
20
2
Order By: Relevance
“…All studies included in this review published between 2012 and 2018. Of all the included studies, only two studies were used retrospective cohort study (24,25) and the rest were used institutional based cross sectional study design (7,10,12,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). From 25 studies, 53381 mothers participated to estimate the prevalence whereas, 11 studies were reported associated factors of C-section in Ethiopia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies included in this review published between 2012 and 2018. Of all the included studies, only two studies were used retrospective cohort study (24,25) and the rest were used institutional based cross sectional study design (7,10,12,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). From 25 studies, 53381 mothers participated to estimate the prevalence whereas, 11 studies were reported associated factors of C-section in Ethiopia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Additionally, Two studies were assessed the association between mother's place of delivery and Csection (7,41). Using 1142 mothers, the pooled odds ratio of indicated that mothers were delivered in private institution were 4.63 times more likely undergoing to C-section as compared to those mothers delivered in public institutions (OR: 4.63, 95%CI: 2.06, 10.29) Fig.…”
Section: Risk Of Bias Assessments Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations